Remaining Large Bone Fragment of a Bony Bankart Lesion in Shoulders With a Subcritical Glenoid Defect: Association With Recurrent Anterior Instability. Issue 1 (January 2022) - Nakagawa, Shigeto; Hirose, Takehito; Uchida, Ryohei; Ohori, Tomoki; Mae, Tatsuo
Background: A preoperative glenoid defect of 13.5% or larger is recognized as a subcritical glenoid defect at arthroscopic Bankart repair (ABR) for collision/contact athletes or military personnel. Purpose: To clarify the prevalence and size of remaining bone fragments in shoulders with a subcritical glenoid defect at recurrent anterior instability and to investigate the influence on postoperative recurrence after ABR for younger competitive athletes. Study Design: Cohort study; Level of evidence, 4. Methods: The study included 96 shoulders with recurrent instability that underwent ABR between July 2011 and March 2018 for shoulders with a subcritical glenoid defect. The patients were divided into 2 groups according to the glenoid defect size (13.5%-<20%, medium; ≥20%, large). The bone fragment size in each defect group was retrospectively investigated and classified into 4 groups (no, 0%; small, >0%-<5%; medium, 5%-<10%; large, ≥10%). The postoperative recurrence rate for each combination of glenoid defect size and bone fragment size was investigated for competitive athletes aged <30 years. The fragments, when present, were repaired to the glenoid. Results: The glenoid defect size was 13.5%-<20% in 60 shoulders (medium defect group) and ≥20% in 36 shoulders (large defect group). The mean bone fragment size was 6.7% ± 5.1% and 8.9% ± 4.9%, respectively ( P = .042). In the medium defect group, there were 15 shoulders (25%) without a bone fragment, 6 shoulders (10%) with a small fragment, 23 shoulders (38.3%) with a medium fragment, and 16 shoulders (26.7%) with a large fragment. In the large defect group, the respective numbers were 2 shoulders (5.6%), 6 shoulders (16.7%), 14 shoulders (38.9%), and 14 shoulders (38.9%). A medium or large bone fragment was more common in the large defect group ( P = .252). Among 64 younger competitive athletes who underwent ABR with a minimum of 2 years of follow-up, postoperative recurrence was recognized in 7 of 38 (18.4%) athletes in the medium defect group, but it was not recognized in any of the 26 athletes in the large defect group ( P = .036). Postoperative recurrence was recognized in 4 of 12 (33.3%) athletes with a small fragment or no fragment and in 3 of 52 (5.8%) athletes with a medium or large fragment ( P = .019). Conclusion: A larger bone fragment frequently remained in shoulders with a subcritical glenoid defect at recurrent instability. The postoperative recurrence rate after ABR for younger competitive athletes was low when a remaining larger bone fragment was repaired.